Institutional Analysis of Legal Change: The Case of Corporate Governance in China - Sonja Opper; Sylvia Schwaag-Serger (Washington University Journal of Law & Policy, 2008)
During the last three decades, China has undergone a period of unprecedented institutional change. The gradual market transition of the economy and China’s integration into the WTO have created a strong demand for new laws and regulations. For institutional economics this period provides a unique opportunity to study the qualities, implications, and driving forces of distinct legal arrangements and their impact on economic development in transition economies. Empirical research not only provides insight into China’s emerging legal system, it also promises important feedback effects for the field of institutional economics. In this Essay we argue that meaningful analysis of legal change in transition economies, such as China’s, must look beyond change of law in the books; it requires analysis of institutional frameworks that shape social behavior, which in turn explain the effectiveness of changes in the law. Using the example of corporate governance, we show that changes in the law have not sufficiently been matched by changes in institutional conditions, explaining why, in spite of far-reaching judicial reform, Chinese corporate governance still displays significant weaknesses in practice.
Keywords: Corporate governance – China; Law reform – China; Institutional economics; Economics – China; Change – China; China